The ATP-dependent RNA helicase HrpB plays an important role in motility and biofilm formation in Xanthomonas citri subsp. citri. Issue 1 (December 2016) - Granato, Laís; Picchi, Simone; Andrade, Maxuel; Takita, Marco; de Souza, Alessandra; Wang, Nian; Machado, Marcos
Abstract Background RNA helicases are enzymes that catalyze the separation of double-stranded RNA (dsRNA) using the free energy of ATP binding and hydrolysis. DEAD/DEAH families participate in many different aspects of RNA metabolism, including RNA synthesis, RNA folding, RNA-RNA interactions, RNA localization and RNA degradation. Several important bacterial DEAD/DEAH-box RNA helicases have been extensively studied. In this study, we characterize the ATP-dependent RNA helicase encoded by thehrpB (XAC0293) gene using deletion and genetic complementation assays. We provide insights into the function of thehrpB gene inXanthomonas citri subsp.citri by investigating the roles ofhrpB in biofilm formation on abiotic surfaces and host leaves, cell motility, host virulence of the citrus canker bacterium and growthin planta . Results ThehrpB gene is highly conserved in the sequenced strains ofXanthomonas . Mutation of thehrpB gene (∆hrpB ) resulted in a significant reduction in biofilms on abiotic surfaces and host leaves.∆hrpB also exhibited increased cell dispersion on solid medium plates.∆hrpB showed reduced adhesion on biotic and abiotic surfaces and delayed development in disease symptoms when sprayed on susceptible citrus leaves. Quantitative reverse transcription-PCR assays indicated that deletion ofhrpB reduced the expression of four type IV pili genes. The transcriptional start site offimA (XAC3241) was determined using rapid amplification of 5′-cDNA Ends (5′RACE). Based on the results offimA mRNA structure predictions, thefimA 5′ UTR may contain three different loops. HrpB may be involved in alterations to the structure offimA mRNA that promote the stability offimA RNA. Conclusions Our data show thathrpB is involved in adherence ofXanthomonas citri subsp.citri to different surfaces. In addition, to the best of our knowledge, this is the first time that a DEAH RNA helicase has been implicated in the regulation of type IV pili inXanthomonas .